Driving Green Purchase Intention in Slow Fashion: The Direct and Moderating Roles of Green Perceived Value and Greenwashing - Velian Zalfa; Rita Komaladewi; Yevis Marty Oesman (Media Ekonomi dan Manajemen, 2026)
The growth of online fashion shopping and increasing concern about sustainability have encouraged interest in slow fashion, yet consumers still face uncertainty in evaluating sustainable product claims on digital platforms. This study aims to examine the effects of electronic service quality, green perceived value, and greenwashing on green purchase intention toward slow fashion products. A quantitative approach was applied through an online survey of 298 Generation Z and Millennial consumers in Jabodetabek, Bandung, and Surabaya who were familiar with but had not purchased local slow fashion products. The data were analyzed using Partial Least Squares Structural Equation Modeling. The findings show that electronic service quality and green perceived value positively influence green purchase intention, while greenwashing has a negative effect. Green perceived value strengthens the relationship between electronic service quality and green purchase intention, whereas greenwashing weakens this relationship. These findings imply that slow fashion brands should improve digital services quality, strengthen perceived sustainability value, and communicate environmental claims transparently to encourage purchase intention.